Propriedades catalíticas de sólidos ácidos na valorização da biomassa - Santiago Neto, Antonio de Brito (2023)
Plant biomass is a highly abundant renewable resource, in evidence as a substitute for fossil fuel energy sources. In this context, the conversion of trioses has been used to identify efficient heterogeneous catalysts. Regarding the conversion of dihydroxyacetone (DHA) to lactic acid in aqueous media, TiO2 has proven to be highly versatile and water tolerant. For this purpose, TiO2-based catalysts were synthesized using an innovative sol-gel method, resulting in Nb-doped solids (x-Nb/TiO2 series). These catalysts were characterized through X-ray diffraction (XRD), Raman spectroscopy, textural analysis, Fourier-transform infrared spectroscopy (FTIR), ammonia and CO2 adsorption microcalorimetry and then, evaluated in the DHA transformation in aqueous media. The results indicated the predominance of the TiO2 anatase phase in the solids, in accordance with their structural properties. Among the doped solids, the 20-Nb/TiO2 catalyst exhibited the highest textural and acidic properties, resulting in a 94% conversion of DHA in 4 hours of reaction, with oligomer formation. In the acetylation of glycerol in the presence of acetic acid to obtain acetins, MPAs supported on aluminosilicate nanotubes were synthesized through wet impregnation. The catalysts were characterized through X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), textural analysis, scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDX), transmission electron microscopy (TEM), temperature-programmed desorption of ammonia (TPD-NH3), and X-ray photoelectron spectroscopy (XPS). Phases related to MoO3 were found through XRD, and FTIR and XPS techniques showed the presence of impregnated H3PMo12O40 on the nanotubes, forming clusters on the catalyst surface and enhancing the textural and acidic properties with increasing MPA content in the support. The catalytic results in the acetylation of glycerol with acetic acid indicated that the supported solids showed glycerol conversion above 5%, with the best performance attributed to 50-MPA/HNT due to its acid and textural properties.